Eksistensi Badan Pengawas Pemilihan Umum dalam Pencegahan Praktik Politik Uang pada Pilkada 2020 di Kabupaten Klaten - Asmorojati, Anom Wahyu; Harianja, Dian Mutiara (Wajah Hukum, 2024)
This study aims to determine the roles, find out obstacles, and explicate the efforts of the Election Supervisory Agency (Bawaslu) in preventing the practice of money politics during the 2020 Regional Elections in the Klaten Regency. This research is empirical legal research with direct field research. Its primary data source is data from interviews with the Bawaslu of Klaten Regency. The results of this study indicate that Bawaslu as a state institution has a duty to carry out supervision, including preventing violations in Regional Elections. The role of the Klaten Regency Bawaslu in preventing violations of money politics practices include providing socialization to all elements of society and forming an Anti-Money Politics Village and a Monitoring Village. In its supervision, the Klaten Regency Bawaslu experienced obstacles such as a lack of human resources, limited budget, and low community participation in supervision. The community itself is still afraid to report if they find violations. Therefore, to overcome these obstacles, Klaten Regency Bawaslu utilize social media to facilitate the socialization to the public, invite the public, candidates, and campaign teams to reject all kinds of money politics practices, and form Anti-Money Politics Villages and Monitoring Villages.